2022
DOI: 10.31219/osf.io/vhn6x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterisation of self-reported improvements in education and health among users of Flo period tracking app: cross-sectional survey

Abstract: Introduction: Low health literacy among girls, women, and people who menstruate is associated with worse reproductive health outcomes. Mobile apps promise tools for improving women’s health literacy, however, there is little information about subscribers’ perceptions of app functionality and its impact on their knowledge and health. Objective: This study aimed to explore knowledge and health improvements related to menstrual cycle and pregnancy, as well as improvements in general health in Flo app users. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
(94 reference statements)
3
2
0
Order By: Relevance
“…These findings remained significant after controlling for covariates such as HRT use, hormonal contraceptive use, supplement use, age, and current comorbidities. These findings are in line with prior research in the field of female health which has demonstrated that symptom monitoring during menopause and use of digital health apps which enable period logging and digital health promoting activities are associated with health improvements (5,6,3,4).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings remained significant after controlling for covariates such as HRT use, hormonal contraceptive use, supplement use, age, and current comorbidities. These findings are in line with prior research in the field of female health which has demonstrated that symptom monitoring during menopause and use of digital health apps which enable period logging and digital health promoting activities are associated with health improvements (5,6,3,4).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, greater weekly engagement with the app was associated with greater reductions in symptoms. These results support previous findings which have suggested that symptom monitoring and use of digital tools which facilitate period logging, and health-promoting digital activities can be beneficial for improving health outcomes, especially relating to psychological and cognitive complaints (5,6,3,4). However, these findings are limited by the observational study design.…”
Section: Discussionsupporting
confidence: 88%
“…Logging periods was also associated with symptom reductions, which supports Zhaunova et al ’s 3 findings. This could suggest that women in the early stage of perimenopause, and therefore, still experiencing regular periods, might experience greater benefits from the app than postmenopausal women.…”
Section: Discussionsupporting
confidence: 85%
“…These results support previous findings which have suggested that symptom monitoring and use of digital tools which facilitate period logging, and health-promoting digital activities can be beneficial for improving health outcomes, especially relating to psychological complaints. 3–6 However, these findings are limited by the observational study design. Therefore, future research should conduct a fully controlled study to further understand the effects of using the Health & Her app to improve health during menopause, with a focus on exploring the app as an adjunct to menopause-specific treatments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation